Evaluating the Impact of Colonialism on Economic Development: A Counterfactual Analysis - Sunny John Kaniyathu (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
Did colonization a ect the patterns of development of the colonized territories. I draw attention to the importance of counterfactuals and claim that assessments of the colonial impact are contingent on the counterfactual employed. Paying attention to counterfactuals enables us to design an empirical strategy to assess the impact of colonialism. Inferences based on non-experimental data may su er from various biases. Statistical models make di erent assumptionsto identify the models and correct for likely biases. Causal effects are sensitive to these assumptions. I apply different matching methods and check for robustness of results. In the sample considered, the analysis indicates that colonialism had a negative on the economic development of the colonized but the causal effect was miniscule in economic terms.
Keywords: 330